Simplified pure spinor b ghost in a curved heterotic superstring background - Berkovits, Nathan [UNESP]; Chandia, Osvaldo (Springer, 2014)
Using the RNS-like fermionic vector variables introduced in arXiv:1305.0693, the pure spinor b ghost in a curved heterotic superstring background is easily constructed. This construction simplifies and completes the b ghost construction in a curved background of arXiv:1311.7012.
Keywords: Superstrings and Heterotic Strings; Conformal Field Models in String Theory